Biomass Allocation Responses to Root Interactions in Wheat Cultivars Support Predictions of Crop Evolutionary Ecology Theory - Zhu, Yong-He; Weiner, Jacob; Jin, Yi; Yu, Ming-Xi; Li, Feng-Min (Frontiers in Plant Science, 2022)
The goal of agriculture is to optimize the population yield, but natural selection has produced active competition among plants, which decreases population performance. Therefore, cultivar breeding should be based on group selection, increasing yield by weakening individual competitive responses. We hypothesize that this has occurred inadvertently to some degree, so modern cultivars have weakened competitive traits and responses, such as reduced root proliferation in response to neighboring roots. We conducted a field experiment with eight cultivars of spring wheat that have been released over the last hundred years, which we grew at two densities. Two contrasting wheat cultivars, a landrace and a modern cultivar, were used in a second field experiment on competition within and between the two cultivars to quantify their competitiveness. Finally, a greenhouse experiment was conducted with these two cultivars gown (a) in mixture and monoculture, (b) at four densities, (c) two watering levels, and (d) with permeable vs. non-permeable soil dividers, to study root proliferation responses to competition. Results of field experiment 1 showed that the population aboveground biomass (AGB) had increased, while belowground biomass had decreased over the course of breeding, so that the root to shoot ratio (R/S) was negatively correlated with the release year of the cultivar. The landrace had stronger competitiveness than the modern cultivar in the field experiment 2. There was clear evidence of root proliferation and a resultant reduction in AGB in response to neighboring roots in the greenhouse experiment, and the modern variety showed less root proliferation in response to neighbors. We conclude that the newer cultivar was a weaker competitor but higher-yielding in two ways: (1) it had higher reproductive effort and therefore less allocation to structures that increase competitive ability, and (2) it had reduced root proliferation in response to the roots of neighboring plants. Our results show that wheat plants change their biomass allocation in response to resource levels and the presence of neighboring roots. The presence of root proliferation in the modern cultivar, albeit less than in the landrace, suggests that further increases in yield via group selection are possible.